2016
DOI: 10.15244/pjoes/60895
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Urban Lake Water Quality Based on in-situ Cyanobacterial and Total Chlorophyll-a Monitoring

Abstract: The aim of this study was to establish a simple and cost-effective method to monitor the effects of harmful algal blooms as exemplifi ed in Lake Powsinkowskie, and to link the monitoring results to potential health risks on the basis of established Alert Level Frameworks.An assessment of the severity of cyanobacterial development in Lake Powsinkowskie (52°9'27"N, 21°5'55"E), located in the Wilanów region, Warsaw, Poland, was performed to illustrate this. An Alert Level Framework based on cyanobacterial chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…It was observed that water hardness had an adverse effect on washing and rubbing fastness when fabric was dyed with both turmeric and eucalyptus extracts. Therefore, based on this study, the use of mordanting/sequestering agent is suggested to enhance the dye uptake and previous studies also revealed a similar trend that mordanting/sequestering can be used to enhance the color strength and color properties [27][28][29][30][31][32][33][34][35][36], and in view of current environmental pollution [37][38][39][40][41][42][43][44][45][46][47][48][49][50], the natural sources should be preferred to avoid a negative impact on the environment.…”
Section: Color Propertiesmentioning
confidence: 67%
“…It was observed that water hardness had an adverse effect on washing and rubbing fastness when fabric was dyed with both turmeric and eucalyptus extracts. Therefore, based on this study, the use of mordanting/sequestering agent is suggested to enhance the dye uptake and previous studies also revealed a similar trend that mordanting/sequestering can be used to enhance the color strength and color properties [27][28][29][30][31][32][33][34][35][36], and in view of current environmental pollution [37][38][39][40][41][42][43][44][45][46][47][48][49][50], the natural sources should be preferred to avoid a negative impact on the environment.…”
Section: Color Propertiesmentioning
confidence: 67%
“…Cyanotoxins generated by cyanobacteria in lagoon water could present a risk to human health (Watzin et al 2006;Mc Quaid et al 2011;Kalaji et al 2016). In situations where the current cyanotoxin concentration is not available, Chl-a is also widely recognized as a surrogate indicator of cyanobacterial density (Wheeler et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of operational procedures is necessary for the effective management and planning of complex water resources systems [1]. Although water losses are a critical parameter that must be considered in the design of water distribution systems, little attention has been given to the consideration of these losses, which can affect the design accuracy [2]. Optimization and numerical simulation are the most powerful methods available for analyzing reservoir systems.…”
Section: Introductionmentioning
confidence: 99%